2009
DOI: 10.5194/amt-2-495-2009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of aerosol properties from MAX-DOAS observations of the Ring effect

Abstract: Abstract. The first quantitative comparison of MAX-DOAS observations of the Ring effect with model simulations is presented. It is performed for a large variety of viewing geometries (solar zenith angles: 45 • to 90 • , elevation angles: 3 • , 6 • , 10 • , 18 • , 90 • ; three different azimuth angles), which allows a comprehensive test of our capabilities to measure and simulate the Ring effect. In addition to the Ring effect, also the observed O 4 absorptions (optical densities) and radiances are compared wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 43 publications
(56 reference statements)
6
95
0
Order By: Relevance
“…Vibrational Raman scattering has been suggested to play a role for zenith sky DOAS measurements of stratospheric absorbers at high SZA (Platt et al, 1997), as well as for liquid water in the oceans (Vountas et al, 2003). Vibrational Raman scattering on gas-phase molecules is today not typically considered in the analysis of MAX-DOAS spectra, which treat only the rotational component of Raman scattering to calculate the Ring reference spectrum (Chance and Spurr, 1997;Vountas et al, 1998;Platt and Stutz, 2008;Wagner et al, 2009). We are unaware of a discussion of vibrational Raman scattering by gas-phase molecules for tropospheric absorbers measured by MAX-DOAS, where in addition to N 2 and O 2 also H 2 O could play a role.…”
Section: Discussion Of Rms Limitations Of Field Measurementsmentioning
confidence: 99%
“…Vibrational Raman scattering has been suggested to play a role for zenith sky DOAS measurements of stratospheric absorbers at high SZA (Platt et al, 1997), as well as for liquid water in the oceans (Vountas et al, 2003). Vibrational Raman scattering on gas-phase molecules is today not typically considered in the analysis of MAX-DOAS spectra, which treat only the rotational component of Raman scattering to calculate the Ring reference spectrum (Chance and Spurr, 1997;Vountas et al, 1998;Platt and Stutz, 2008;Wagner et al, 2009). We are unaware of a discussion of vibrational Raman scattering by gas-phase molecules for tropospheric absorbers measured by MAX-DOAS, where in addition to N 2 and O 2 also H 2 O could play a role.…”
Section: Discussion Of Rms Limitations Of Field Measurementsmentioning
confidence: 99%
“…aeronomie.be/spectrolab/o2.htm) were used. Recently, Wagner et al (2009) and found that the retrieved O 4 SCDs were systematically too high to match the model simulation even under pure Rayleigh conditions, at least at the times and locations of their MAX-DOAS observations. These differences might be induced in the DOAS retrieval by uncertainties in the absolute values of the O 4 cross sections.…”
Section: Doas Analysismentioning
confidence: 99%
“…However, the reason for the uncertainty is not yet well understood. The uncertainty is typically corrected by multiplying the O 4 absorption cross section with a constant correction factor (Wagner et al, 2009Clémer et al, 2010;Chan et al, 2015;Wang et al, 2016). By comparing the measured and modeled O 4 absorptions, we estimated that the literature O 4 absorption cross section was underestimated by 20 %.…”
Section: Ancillary Datamentioning
confidence: 99%